A simulation quantities/price generation cost model for reinforced concrete framed structures - Bowen, Paul; Taylor, RG (Acta Structilia, 1994)
Conventional approaches to the measurement of construction work are critically examined, and the risk and uncertainty in the pricing of these measured items discussed. Implications for future practice are considered, and a model framework for purposes of estimating and tender documentation using statistical procedures is proposed. The potential use of simulation is examined by means of a practical example which draws upon data relating to reinforced concrete framed office buildings. The developed model is examined and proposals for future development presented.